Knowledge management system’s implementation in private universities through SECI model - Rukmana, Aan; Widhianto, Chandra Wibowo (Indonesian Journal of Multidisciplinary Science, 2023)
The purpose of this research is to analyze the implementation of the Knowledge Management System (KMS) at x University in Jakarta. The research model implemented is qualitative research. Research data were collected through observation, interviews, documentation and triangulation techniques. The technical analysis of the collected data uses data reduction with the SECI model from Nonaka and Takeuci (Socialization, Externalization, Combination and Internalization), data display and drawing conclusions. These data were tested to ensure the validity of the data by testing the credibility, transferability test and confirmability test. The research results prove that x University has implemented a Knowledge Management System using the SECI Model. These results are a new theory originating from the field (grounded theory).